Pembrolizumab and Chemotherapy with Radiology Comparative Analysis in Patients with Untreated Metastatic Triple Negative Breast Cancer - Muhammad Usama Ur Rehman, Ibrar Ali, Hamna Zia (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This research compares the results of radiography, chemotherapy, and pembrolizumab usage in patients with metastatic triple-negative breast cancer who have not previously received any treatment. Study Design: Observational/Comparative study. Place and Duration: Sadiq Abbasi Hospital Bahawalpur. November 2021-May 2022 Methods: 100 females between the ages of 20 and 80 participated in this study. Included were patients with metastatic triple-negative breast cancer who had not yet begun therapy. Patients were split into two groups equally. 50 patients in group A got pembrolizumab 200 mg every two weeks while 50 patients in group B got chemotherapy (75 mg of Adriamycin) every 21 days for six months. Patients were followed up with often. Post-treatment results for both groups were evaluated and contrasted with regard to effectiveness, disease control, mortality, and recurrence rate. The full set of data was analyzed using SPSS 20.0. Results: We found that efficacy in group A was higher in 22 (44%) cases as compared to group B in 15 (30%) cases. Frequency of partial recovery in both groups were 14 (28%) and 10 (20%). Frequency of stability in disease among patients of group B was higher 16 (32%) as compared to group A 9 (18%). Mortality and recurrence rate was lower in pembrolizumab group as compared to chemotherapy group with p value <0.004. Frequency of adverse outcomes in group A was higher. Conclusion: We came to the conclusion from this study that the usage of pembrolizumab injection for the breast cancer treatment was beneficial and successful in terms of low mortality with recurrence rate and greater number of recovery, although rate of stability among illness was higher in chemotherapy group. Decreased illness rate was achieved with both therapies. Keywords: Mortality, Chemotherapy, Recurrence, Pembrolizumab, Breast Cancer